Practical threat detection engineering : a hands-on guide to planning, developing, and validating detection capabilities /: a hands-on guide to planning, developing, and validating detection capabilities. (2023) - Roddie, Megan; Deyalsingh, Jason; Katz, Gary J
No abstract available